Studi Tentang Ekologi dan Habitat Planaria, Sp. di Subang: Kelimpahan dan Biomassa Merupakan Indikator Kualitas Air Bersih - Hertien Koosbandiah Surtikanti; Ulfah Bahabazi (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
Planaria sp. in Bukit Tunggul (Lembang) is rare within 10 years. This animal is sensitive to polluted water. Beside that, the number of this animal is decreasing due to alteration of landuse and climate change. This animal plays an important role as a bioindicator for clean water and as a media in learning of biology in high school as well as in university. Due to these need, study on ecology and distribution of Planaria sp. is done in Panaruban water fall, Subang. The sampling location is limited only at Cimuja, Karembong, Sawer and Goa Badak, which have an environment characteristics variation. Observations are done including water quality chemically, land use, and climatic factors within 3 times monthly. Planaria sp. counting is done stratified random sampling using a 1x1 m quadran. The number and biomass of Planaria sp. related to climatic factors are discussed. In general, it can be concluded that, abiotic environmental factors contributes to the abundance and biomass of Planaria sp.